Stiff Person Syndrome and Other Anti-GAD–Associated Neurologic Disorders - Dayalu, Praveen; Teener, James W. (Seminars in Neurology, 2012)
Antibodies directed against glutamic acid decarboxylase (GAD) are present in many patients with stiff person syndrome and increasingly found in patients with other symptoms indicative of central nervous system (CNS) dysfunction, such as ataxia. The classic clinical features of stiff person syndrome include muscular stiffness with superimposed painful muscular spasms. Gait is often impaired. Other CNS disorders associated with GAD antibodies include progressive encephalomyelitis with rigidity and myoclonus (PERM), limbic encephalitis, and even epilepsy. Glutamic acid decarboxylase is the rate-limiting enzyme in the production of gamma-aminobutyric acid (GABA), the primary inhibitory neurotransmitter. Presumably, antibodies directed against GAD impair GABA production, but the precise pathogenic mechanism of GAD-antibody-related neurologic disorders is uncertain. Many patients respond to treatment with immunomodulating therapy. Symptomatic treatment with agents that enhance GABA activity, such as benzodiazepines and baclofen, is also helpful for many patients.
Keywords: GAD antibodies; stiff person syndrome; muscle stiffness; cerebellar ataxia; progressive encephalomyelitis with rigidity and myoclonus; limbic encephalitis